2011
DOI: 10.1210/jc.2010-2802
|View full text |Cite
|
Sign up to set email alerts
|

Serum IGF-I Levels Correlate to Improvement of Functional Outcome after Ischemic Stroke

Abstract: A high s-IGF-I during the rehabilitation phase of stroke correlates to better recovery of long-term function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(135 citation statements)
references
References 25 publications
7
123
3
2
Order By: Relevance
“…99 High serum levels of insulin-like growth factor 1 after stroke are associated with neurological recovery and better functional outcome. 100,101 In experimental stroke, insulin-like growth factor 1 treatment improved motor recovery, paralleled by enhanced neovascularization and neurogenesis. 102,103 However, because of its inability to pass through blood-brain barrier, insulin-like growth factor 1 was administered intranasally starting 10 minutes after stroke induction 102 or by adeno-associated virus-mediated gene transfer 3 weeks before stroke.…”
Section: Growth Factorsmentioning
confidence: 99%
“…99 High serum levels of insulin-like growth factor 1 after stroke are associated with neurological recovery and better functional outcome. 100,101 In experimental stroke, insulin-like growth factor 1 treatment improved motor recovery, paralleled by enhanced neovascularization and neurogenesis. 102,103 However, because of its inability to pass through blood-brain barrier, insulin-like growth factor 1 was administered intranasally starting 10 minutes after stroke induction 102 or by adeno-associated virus-mediated gene transfer 3 weeks before stroke.…”
Section: Growth Factorsmentioning
confidence: 99%
“…The design of Sahlgrenska Academy Study on Ischemic Stroke (SAHLSIS) has been reported elsewhere (4,10). Briefly, patients (!70 years) with first-ever or recurrent acute IS were recruited consecutively at four Stroke Units in western Sweden between 1998 and 2008 (nZ844).…”
Section: Methodsmentioning
confidence: 99%
“…For the first 600 cases, data on functional outcome (modified Rankin Scale (mRS)) after 3 and 24 months or stroke severity (Scandinavian Stroke Scale (SSS)) acutely were available. From these subjects, s-IGF1 levels in 407 patients and in 40 randomly selected controls were available from a previous study (4). The s-IGF1s of these subjects were analyzed in 2008 in one series of experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations